Concerts and Inadvertent Secularization: Religious Music in the Entertainment Market of Eighteenth-Century Paris. - Pesic, Andrei (Past & Present, 2021)
Public concerts offer a new perspective on the controversial subject of secularization and the Enlightenment. From 1725–90, the Concert spirituel in Paris, one of the earliest and most famous concert series in Europe, presented a mixture of sacred and secular music when other entertainments were forbidden during religious holidays. Over the course of the century, the proportion of religious works in its repertoire declined significantly. Whereas previous interpretations tended to describe secularization as resulting either from battles between philosophes and the Church or from broader declines in belief, this article casts doubt on these explanations by showing the heterogeneous composition of the Concert's audience. Instead, it depicts a process of 'inadvertent secularization' stemming from market pressure, in this case due to the multiplication of new concert series and other entertainments in Paris during the second half of the eighteenth century. This framework accounts for secularization at the institutional level without assuming that the society as a whole was marked by declining Christian belief. Bringing together the study of markets and religion reveals how multiple logics increased the autonomy of artistic fields formerly subject to religious constraints.